Silviculture and community forestry: looking backwards, looking forwards - Gilmour, D. (Banko Janakari, 2018)
Silviculture is about the deliberate manipulation of a forest to achieve defined objectives. It can be thought of as the art of producing and tending a forest. The notion of “appropriate” silviculture is very important when considering silviculture for community forests because silvicultural approaches and prescriptions need to be appropriate for local users while also ensuring that they promote the long term sustainability of the forest. Experience suggests that not all community forests require the application of sophisticated silvicultural regimes or the use of inventory data to schedule yields. Many can be managed perfectly well by the application of very simple silvicultural regimes and little or no need to collect inventory data. The needs of the most complex situation (sophisticated silvicultural system and inventory) should not be the model for all community forestry silviculture. At best, conventional silvicultural regimes and inventory practices require major revision for community forestry. It is clear that community forestry will achieve its full potential only if a holistic view is taken and a number of enabling conditionalities are met. These include: secure tenure, an enabling regulatory framework, strong governance, viable technology (including appropriate silviculture), adequate market knowledge and a supportive bureaucracy. These all need to be present for community forestry to operate at its full potential to deliver the biophysical and socio-economic outcomes that are expected of it. Viable technology, including appropriate silviculture informed by good science, is one of these important conditionalities but it is not the only one. Sustainable outcomes require much more than the application of technical forestry. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 6-14